Development of a plant-wide steady-state wastewater treatment plant design and analysis program - Wu, William Ying Xin (Department of Civil Engineering, 2015)
Models are used as prognostic and diagnostic tools in order to design, analyse and optimise the biological and physical processes in a wastewater treatment plant (WWTP). This is done in order to save time and money and to improve the understanding of the behaviour of the treatment system. There are two categories of models in wastewater (WW) treatments, steady-state and dynamic models. (i) Dynamic models consist of sophisticated mathematical solvers and are structured for the optimisation of WWTP’s and not for system sizing. (ii) Steady-state models comprise simple and explicit algebraic equations. With these equations, high-level answers are found easily and quickly but with a much lower level of input information. Hence, steady-state models allow for system sizing and are powerful pre-processors for dynamic models. They can generate the overall WWTP scheme, main system defining parameters, and the initial conditions for starting the dynamic simulation. Currently, there is a lack of a plant-wide steady state design (PWSSD) program. Numerous steady-state models for the different unit processes exist; however, they are yet to be integrated and presented in one holistic software package for the plant-wide design (and analysis) of WWTP. The availability of such program will be extremely beneficial to WWTP engineers as it can be used as a standalone tool for the steady state design, system sizing and capacity estimation, or as a pre-processor to generate the plant wide WWTP initial conditions for dynamic simulation. To fill the above-mentioned software gap, a PWSSD program was developed within the Excel/VBA environment. The developed PWSSD program integrates various steady-state wastewater treatment models with an expert-guided user-interface, thereby creating a platform for step-by-step assisted interaction and exploration of the models. This program draws upon a large body of literature regarding the modelling of wastewater treatment processes. The current version of the program (1) caters for commonly used AS configurations (MLE, JHB and UCT) in South Africa. The steady-state AS models are holistically linked to important upstream and downstream biological and non-biological treatment processes.